2021
DOI: 10.3389/fcell.2021.658481
|View full text |Cite
|
Sign up to set email alerts
|

Hippo-Independent Regulation of Yki/Yap/Taz: A Non-canonical View

Abstract: Initially identified in Drosophila, the Hippo signaling pathway has emerged as an evolutionarily conserved tumor suppressor pathway that controls tissue growth and organ size by simultaneously inhibiting cell proliferation and promoting cell death. Deregulation of Hippo pathway activity has been implicated in a wide range of human cancers. The core Hippo pathway consists of a kinase cascade: an upstream kinase Hippo (Hpo)/MST1/2 phosphorylates and activates a downstream kinase Warts (Wts)/Lats1/2, leading to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 100 publications
1
15
0
Order By: Relevance
“…The hippo pathway-related genes in the negative growth-related brown module suggested their possible roles in the sexual growth difference of C. semilaevis . The hippo pathway (conserved in Drosophila melanogaster and mammals) has been shown to regulate cell growth, fate decision, organ size, and regeneration ( Halder and Johnson, 2011 ; Ma et al, 2019 ; Cho and Jiang, 2021 ). Besides, tissue overgrowth phenotypes in D. melanogaster are promoted by the following factors: 1) The mutation of its core kinase components, such as warts ( wts ) ( Justice et al, 1995 ; Xu et al, 1995 ), hippo ( hpo ) ( Harvey et al, 2003 ), and salvador ( sav ) ( Tapon et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hippo pathway-related genes in the negative growth-related brown module suggested their possible roles in the sexual growth difference of C. semilaevis . The hippo pathway (conserved in Drosophila melanogaster and mammals) has been shown to regulate cell growth, fate decision, organ size, and regeneration ( Halder and Johnson, 2011 ; Ma et al, 2019 ; Cho and Jiang, 2021 ). Besides, tissue overgrowth phenotypes in D. melanogaster are promoted by the following factors: 1) The mutation of its core kinase components, such as warts ( wts ) ( Justice et al, 1995 ; Xu et al, 1995 ), hippo ( hpo ) ( Harvey et al, 2003 ), and salvador ( sav ) ( Tapon et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified that O-GlcNAcylation at the Ser109 site ( 34 ) and Thr241 site ( 35 ) of YAP stabilized YAP by antagonizing its Hippo-dependent phosphorylation, which incurred high-glucose-induced liver tumorigenesis. Interaction between YAP and O-GlcNAcylation links glucose abundance to Hippo signaling activity and tumorigenesis ( 36 ). Besides, YAP upregulates enzymes in glycolysis ( 37 ), including some critical rate-limiting enzymes.…”
Section: Hippo-yap-regulated Tumor Survivalmentioning
confidence: 99%
“…Following activation and interaction with partner transcription factors, the cofactors YAP and TAZ are then rendered able to regulate apoptosis, motility, growth, and cell proliferation. We should keep in mind that transcriptional activity of Yap and Taz can be modulated via other signaling pathways, which are also “non-canonical” pathways (for a review, please see [ 112 , 227 ]).…”
Section: Hippo Signalingmentioning
confidence: 99%